2014
DOI: 10.1111/jsm.12567
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Vasectomy on the Sexual Life of Couples

Abstract: Introduction There are several contraceptive methods to prevent pregnancy, reversible as well as nonreversible ones. The sexual satisfaction of couples is affected by many types of contraceptives used. Aim The aim of this study was to evaluate prospectively the effect of vasectomy on the sexual life and satisfaction of couples. Methods Seventy-six couples too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…This was illustrated in an Austrian study of 76 couples who were subjected to validated surveys about male and female sexual function following vasectomy. While there was no change in the sexual desire domain in men, there was a statistically significant increase in women (6.6 vs. 7.6, P < 0.05) [14]. One explanation could be increased libido in women who have ceased oral contraceptive (OCT) use following their partner's vasectomy, as OCTs have been associated with decreased female libido [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was illustrated in an Austrian study of 76 couples who were subjected to validated surveys about male and female sexual function following vasectomy. While there was no change in the sexual desire domain in men, there was a statistically significant increase in women (6.6 vs. 7.6, P < 0.05) [14]. One explanation could be increased libido in women who have ceased oral contraceptive (OCT) use following their partner's vasectomy, as OCTs have been associated with decreased female libido [18].…”
Section: Discussionmentioning
confidence: 99%
“…While it is true that post‐vasectomy erectile dysfunction has been reported, this has been largely attributed to psychologic rather than physiologic factors [11]. Moreover, multiple studies have explored the impact of vasectomy on subsequent male sexual function and satisfaction and found unchanged or improved sexual function with high satisfaction rates [12–14].…”
Section: Introductionmentioning
confidence: 99%
“…[ 17 19 ] Several studies undertaken in recent years have also confirmed that men after undergoing a vasectomy experience markedly improved erectile function, orgasms, and sexual satisfaction and feel safer and more confident in their sexual lives after surgery. [ 8 , 11 , 12 , 13 , 20 ] Their female partners reported marked improvements in terms of sexual arousal, satisfaction, and orgasm, as well as lubrication and libido. In addition, Guo et al [ 9 ] showed that men who had undergone a vasectomy experienced more instances of sexual contact per month than men who had not undergone a vasectomy.…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] A massive number of studies have shown that vasectomy did not affect male sexual function, and interestingly, had a positive effect on the sexual function of the female partners. [ 8 ] A key factor may be the anxiety of women about unwanted pregnancies was reduced, and women's libido improved somewhat, and they were more willing to cooperate with men in sex. [ 9 ]…”
Section: Introductionmentioning
confidence: 99%
“…condoms, withdrawal, and vasectomy) and, as such, hold the potential to disrupt notions of the feminized responsibility for contraception. This oversight is particularly consequential because male body-based methods are widely used (Higgins et al, 2014; Jones, Lindberg, & Higgins, 2014), have high rates of satisfaction (Al-Ali et al, 2014), and/or are very effective in preventing pregnancy (Trussell, 2011). They also each have features that many women report as extremely important to them in a contraceptive method (Lessard et al, 2012).…”
mentioning
confidence: 99%